Effects of p21-activated kinase 1 inhibition on 11q13 amplified ovarian cancer cells - Prudnikova, Tatiana Y. (Oncogene, 2015)
p21-activated kinases (PAKs) are Cdc42/Rac–activated serine-threonine protein kinases that regulate of several key cancer-relevant signaling pathways, such as the Mek/Erk, PI3K/Akt, and Wnt/b-catenin signaling pathways. Pak1 is frequently overexpressed and/or hyperactivated in different human cancers, including human breast, ovary, prostate, and brain cancer, due to amplification of the PAK1 gene in an 11q13 amplicon. Genetic or pharmacological inactivation of Pak1 has been shown to reduce proliferation of different cancer cells in vitro and reduce tumor progression in vivo. In this work, we examined the roles of Pak1 in cellular and animal models of PAK1-amplified ovarian cancer. We found that inhibition of Pak1 leads to decreased proliferation and migration in PAK1 amplified/overexpressed ovarian cancer cells, and has no effect in cell that lack such amplification/overexpression. Further, we observed that loss of Pak1 function causes 11q13 amplified ovarian cancer cells to arrest in the G2/M phase of the cell cycle. This arrest correlates with activation of p53 and p21(Cip) and decreased expression of cyclin B1. These findings suggest that small molecule inhibitors of Pak1 may play a therapeutic role in the ~25% of ovarian cancers characterized by PAK1 gene amplification.